PENINGKATAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS IV SD NO. 2 BENG GIANYAR TAHUN PELAJARAN 2015/2016 - Desak Putu Rohika (Universitas Pendidikan Ganesha, 2017)
This study aims to determine the yield increase fourth grade students learn science even in SD No. 6 Bunutan after the implementation of cooperative learning model Student Team Achievement Division (STAD). This is the kind of research is classroom action research was conducted in two cycles. Each cycle consists of planning, action, observation, and reflection. The study involved a fourth grade student No.. 6 Bunutan which totaled 26 people. Data collection methods used for science learning outcomes is a test method. Data were analyzed using descriptive quantitative method. The results showed that, the implementation of STAD models can improve science learning outcomes. In the first cycle, the average value of 68.27 students belonging to the category of being and mastery learning of 73.08%. In the second cycle the average value of 82.5 students belonging to either category and mastery learning by 100%. Average student learning outcomes from the first cycle to the second cycle increased by 14.23%, and mastery learning from cycle I to cycle II of 26.92%.